Суржик у мовній комунікації України: про один австрійсько-німецький проєкт і не тільки - Šumarova, Natalija; Rojter, Til′mann (Wiener Slawistischer Almanach, 2024)
The article is about a project meeting of an international research project into Ukrainian-Russian mixed speech (Surzhyk) carried out in 2019–2024 by researchers of the University of Klagenfurt (Austria) and the Carl von Ossietzky University at Oldenburg (Germany). Emphasis is placed on the variety of views of European and Ukrainian researchers on the phenomenon of mixing two languages and the perspectives of variational sociolinguistics.